Nigerian public finance - Okigbo, P. N. C. (Evanston [Ill.] Northwestern University Press, 1965)
The approach adopted in this book is both historical and analytical - to offer a guide to the history of taxation in Nigeria, to examine the complex fiscal relationships in a federal system to the growth of the economy as a whole and to the finance of development.
Bibliographical footnotes.
osc 9/6/17
Loans
Keywords: Finance, Public; Nigeria